2022
DOI: 10.1055/s-0042-1755324
|View full text |Cite
|
Sign up to set email alerts
|

The preoperative neutrophil-to-lymphocyte ratio predictive value for survival in patients with brain metastasis

Abstract: Background The neutrophil-to-lymphocyte (NLR), monocyte-to-lymphocyte (MLR), platelet-to-lymphocyte ratio (PLR), and red blood cell distribution width (RDW) have been previously studied as predictors of survival in different malignancies. Objective The aim of this study was to evaluate the predictive value of these hematologic inflammatory biomarkers for patients with brain metastases (BM). Methods We reviewed a consecutive cohort of patients at Instituto do Cancer do Estado de São Paulo (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The literature indicates that these inflammatory indices could be independently used to distinguish the preinvasive lesions in the larynx, cervix, and endometrium from their invasive counterparts [39][40][41]. Also, NLR, MLR, PLR, and SII could be used to predict certain cancer prognoses [16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature indicates that these inflammatory indices could be independently used to distinguish the preinvasive lesions in the larynx, cervix, and endometrium from their invasive counterparts [39][40][41]. Also, NLR, MLR, PLR, and SII could be used to predict certain cancer prognoses [16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Even if the role of neutrophils in cancer is ambiguous, a high neutrophil-to-lymphocyte ratio (NLR) is related to a poorer prognosis for various cancers, such as breast cancer, colorectal cancer, malignant melanoma, and gynecological cancer [16,17]. Likewise, a high monocyte-to-lymphocyte ratio (MLR) and a high platelet-to-lymphocyte ratio (PLR) are also considered valuable prognostic markers in multiple cancers, such as head and neck, gastric, colorectal, and brain metastasis [18][19][20][21]. Recently, the systemic immune-inflammation index (SII), which takes into account the platelet count, has been regarded as a superior prognostic factor for solid tumors, such as esophageal, gynecological, and triple-negative breast cancer, and predicts the response to immunotherapy [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, NLR seems to be a more decisive prognostic marker than PLR in certain studies. [7][8][9] At the present study, we gathered data on NLR, PLR, Red Cell Distribution Width-Coefficient of Variation (RDW-CV at various stages including pre-operatively, post-operatively, and prior to specific adjuvant treatments. Our objective was to investigate the potential influence of these hematological markers on the Overall Survival (OS) and Progression-Free Survival (PFS) in glioblastoma patients, thereby contributing to a deeper understanding of their prognostic significance in this context.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from these studies have consistently revealed that elevated levels of the NLR and PLR before treatment are associated with less favorable outcomes in these patients. Notably, the NLR seems to be a more decisive prognostic marker than the PLR in certain studies [7][8][9].…”
Section: Introductionmentioning
confidence: 99%